PENGARUH WAKTU EKSTRAKSI DAN KONSENTRASI ETANOL MENGGUNAKAN METODE MICROWAVE ASSISTED EXTRACTION (MAE) TERHADAP AKTIVITAS ANTIOKSIDAN EKSTRAK RAMBUT JAGUNG (Zea mays L.) - Kristanti, Yessica; Widarta, I Wayan Rai; Permana, I Dewa Gede Mayun (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 1 (2019): Jurnal ITEPA, 2019)
This research was conducted to determine effect of the extraction time and ethanol concentration on antioxidant activity of corn silk extract and to obtain extraction time and ethanol concentration using Microwave Assisted Extraction (MAE) that can produce extract with the highest antioxidant activity. The experimental design used in this research was a completely randomize design, which consisted of two factors. The fisrt factor was the concentration of ethanol which consisted of 5 level that namely ethanol 30%, 45%, 60%, 75%, and 90%. The second factor was the time of extraction which consisted of 3 level namely 8, 13 and 18 minutes. Data were analyzed with analysis of variance that followed by Duncan test. The result showed that the best treatment of corn silk extract is extraction by ethanol 90% for 18 minutes using MAE which the highest resulted rendemen was 24.54%, total phenol was 159.65 mg GAE/g extract, total flavonoid was 149 mgQE/g extract, antioxidant activity was 70.18%, and the IC 50 value 64.806 ppm.